PERAN KKN UINSU: MEMBANGUN SISWA BERAKHLAK MULIA DAN ANTI-BULLYING DI MIS AL HIKMAH DESA UJUNG TERAN - Panggabean, Alwi Andika; Andy, Safria; Nurzanah, Laila; Ananda, Nabila Tri; Saragih, Lutfiah Irwani (Smart Education, 2025)
Abstract: This study aims to identify the forms of bullying that occur among elementary school students, measure students' perceptions of bullying, and determine the age group most vulnerable to bullying at MIS Al-Hikmah in Ujung Teran Village, Merdeka District, Karo Regency. Through awareness-raising activities conducted by students from the University of Islam Negeri Sumatera Utara's Community Service Program, it was found that bullying most frequently takes the form of physical and social teasing, particularly among fifth and sixth graders. The majority of students (86%) still view bullying as harmless banter without realizing its negative consequences. This study emphasizes the importance of character education based on noble moral values, enhancing students' understanding of bullying, and the active role of teachers, parents, and the school environment in creating a safe and supportive learning environment. The results of the awareness campaign demonstrate the potential for increasing students' awareness and promoting sustainable bullying prevention in Islamic-based elementary school environments. Keywords: elementary school bullying, awareness campaign character education, islamic education bullying prevention Abstrak: Penelitian ini bertujuan untuk mengidentifikasi bentuk-bentuk bullying yang terjadi di kalangan siswa sekolah dasar, mengukur persepsi siswa terhadap bullying, serta mengetahui kelompok usia yang paling rentan terhadap perundungan di MIS Al-Hikmah Desa Ujung Teran, Kecamatan Merdeka, Kabupaten Karo. Melalui kegiatan sosialisasi yang dilaksanakan oleh mahasiswa Kuliah Kerja Nyata Universitas Islam Negeri Sumatera Utara, ditemukan bahwa bullying paling sering berbentuk ejekan fisik dan sosial, terutama pada siswa kelas 5 dan 6. Sebagian besar siswa (86%) masih menganggap bullying sebagai candaan tanpa menyadari dampak negatifnya. Penelitian ini menekankan pentingnya pendidikan karakter berbasis nilai akhlak mulia, peningkatan pemahaman siswa mengenai bullying, serta peran aktif guru, orang tua, dan lingkungan sekolah dalam menciptakan suasana belajar yang aman dan suportif. Hasil sosialisasi menunjukkan potensi positif dalam meningkatkan kesadaran siswa dan mendorong pencegahan bullying yang berkelanjutan di lingkungan sekolah dasar berbasis pendidikan Islam. Kata kunci: bullying sekolah dasar, sosialisasi pendidikan karakter, pendidikan islam pencegahan bullying